The Application of GIS and Remote Sensing in a Spatiotemporal Analysis of Coastline Retreat in Rufisque, Senegal - Koulibaly, Cheikh Tidiane; Ayoade, Johnson O. (Geomatics and Environmental Engineering, 2021)
This paper is aimed at analyzing the phenomenon of shoreline retreat in the locality of Rufisque from 1978 to 2018 mainly using geospatial data and field visits. A set of Landsat images from different dates at 10 year intervals was then acquired through the United States Geological Survey platform and shoreline change analysis was run using the Digital Shoreline Analysis System. In addition to that desktop work, interactions with local residents allowed the determination of ongoing adaptation strategies actually in place to cope with coastal erosion. The study showed that Rufisque is subject to serious rates of erosion reaching âˆ’19.48 m/year from 1978‑1988, close to âˆ’8 m/year from 1988‑1998, âˆ’5.88 m/year from 1998‑2008 and âˆ’6.67 m/year from 2008‑2018. Beside that coastal erosion, it has been noticed that the coastline also experienced in some of its parts cases of accretion reaching 4.94 m/year for 1988‑1998, 7.29 m/year from 1998‑2008 and 7.68 m/year during the period 2008‑2018. In terms of surfaces, Rufisque´ shoreline respectively lost 156.81 ha (1978‑1988), 80.55 ha (1988‑1998), 6.94 ha (1998‑2008), 12.93 ha (2008‑2018) and in the same note gained 2.86 ha (1988‑1998), 32.51 ha (1998‑2008) and 19.16 ha (2008‑2018) attesting to the fact that the coastline is subject to both spatiotemporal changes. Finally, this study also reveals that while authorities´ reaction is taking place at much lower pace, local communities are actually using their ingenuity to put in place strategies to tackle coastal erosion.